The distribution of geographic information systems data in a computer communications network. - Veenendaal, Bert (Curtin University, 1999)
Geographic information systems (GIS) are developing in a rapidly expanding distributed environment. With the ever-increasing growth of computer networks and the Internet in particular, it is imperative that GIS take advantage of distributed data technologies to provide users and applications with shared and improved access to geographic data.Geographic data distribution design is concerned with determining what data gets placed at which computer network sites and involves the issues of data partitioning, allocation and dynamic migration. Partitioning is concerned with how data, or fragments of the data, are apportioned to partitions. These partitions must then be assigned to network sites in an allocation process. Because data usage and access changes by applications in a dynamic environment, migration strategies are necessary to redistribute the data. In order for data distribution to reflect current usage patterns of applications, the design process must obtain and accumulate data usage information from applications.This dissertation first details the predicate fragmentation (PF) model. The core of the model is the PF tree that has been developed and implemented to store and maintain usage information. User predicates, obtained from application queries, are inserted into the tree and primitive predicates can be identified from the tree. These primitive predicates define the fragmentation from which a data distribution can be determined. Predicate insertion and pruning operations are essential to the maintenance of the tree structure.A methodology that uses the PF model to obtain a partitioning, allocation and migration strategy is then outlined. The fragments identified from the PF trees are aggregated into partitions that are then assigned to individual network sites using a site access allocation strategy. A dynamic migration strategy then uses changes in the PF trees to identify the data that must be migrated to a new site in order to accommodate the changing application environment.The implementation of the geographic data distribution methodology is referred to as GEODDIS. The methodology was tested and evaluated using a mineral occurrence application called GEOMINE which was developed with the ArcInfo GIS. The results indicate that geographic data distribution performs well when successive applications have similar data usage requirements. The implementation of the geographic data distribution methodology is referred to as GEODDIS. The methodology was tested and evaluated using a mineral occurrence application called GEOMINE which was developed with the ArcInfo GIS. The results indicate that geographic data distribution performs well when successive applications have similar data usage requirements. For applications with very different data usage patterns, the performance decreases to the worst case scenario where all the data must be transferred to the site where it is used. The tree pruning and data migration operations are essential to maintaining a PF tree structure and distribution that reflects the current data usage of applications.